Online Communities Of Practice And Eel Teachers - RAHMANI , Asma (مجلة العلوم الاجتماعية والانسانية, 2022)
This paper involves an action research that aims at encouraging teachers to investigate the benefits of using the Online Communities of Practice to boost their professionalism and adopt them. Besides, This study seeks to provide a conceptualization of professional process in the field of teaching English as a foreign language. Also, it attempts to gain more insights into how Foreign Language teachers perceive professionalism. Empirical data are gained through an administered questionnaire to a randomly selected sample of thirty teachers from the Department of English at Batna -2 University, Algeria. This questionnaire examines teachers’ awareness, attitudes and readiness towards adopting online community of practice to develop professional skills. Ultimately, the obtained results show that teachers define professionalism differently. Moreover, the results encourage and recommend the integration of Online Community of Practice into foreign language teaching to assist teachers in perfecting their mission and update their professionalism